Identification of Trombospondin-1 as a Novel Amelogenin Interactor by Functional Proteomics - Capolupo, Angela; Cassiano, Chiara; Casapullo, Agostino; Andreotti, Giuseppina; Cubellis, Maria V.; Riccio, Andrea; Riccio, Raffaele; Monti, Maria C. (Frontiers in Chemistry, 2017)
Amelogenins are a set of low molecular-weight enamel proteins belonging to a group of extracellular matrix (ECM) proteins with a key role in tooth enamel development and in other regeneration processes, such as wound healing and angiogenesis. Since only few data are actually available to unravel amelogenin mechanism of action in chronic skin healing restoration, we moved to the full characterization of the human amelogenin isoform 2 interactome in the secretome and lysate of Human Umbilical Vein Endothelial cells (HUVEC), using a functional proteomic approach. Trombospondin-1 has been identified as a novel and interesting partner of human amelogenin isoform 2 and their direct binding has been validated thought biophysical orthogonal approaches.